Mathematical Modeling of Effective Distribution System for Resources and Facilities in Disaster Management by using Optimization Techniques - Rajan Singh, B.K. Singh, Shubham Kumar, Vipin Kumar (Mathematical Statistician and Engineering Applications, 2022)
Emergency resources allocation is essential to the emergency rescue effectiveness, and it has become a research topic for emergency rescue. Emergency resource is important for people when any disaster occurs. Considering, dynamic demand, emergency resource allocation schedule is more challenging. The main problem is to determine the optimal stock of emergency resource for a supplier centers to improve the relief efforts. This paper studies the dynamic demand and which is defined as a set. Then an emergency resource allocation model with some uncertain data is presented. Finally, a case study is taken to show the actual working of the presented model.